Dendronized azochromophores with aromatic and perfluoroaromatic fragments: Synthesis and properties demonstrating ArArF interactions. (March 2019) - Laipniece, Lauma; Kampars, Valdis; Belyakov, Sergey; Tokmakovs, Andrejs; Nitiss, Edgars; Rutkis, Martins
Abstract: Syntheses of four new dendronized azochromophores were performed from 2-(2-amino-5-nitrophenoxy)ethanol, 2-[methyl(phenyl)amino]ethanol, 3, 5-bis(benzyloxy)benzoic acid and 3, 5-bis[(pentafluorophenyl)methoxy]benzoic acid using azo coupling reaction and ester formation reaction in presence of N, Nʹ -dicyclohexylcarbodiimide and 4-(dimethylamino)pyridine. Arene-perfluoroarene (ArAr F ) interactions are demonstrated in single crystal structure of dendronized azochromophore between pentafluorophenyl fragment and acceptor part of the azochromophore. The effect of ArAr F interactions becomes apparent in thermal and nonlinear optical properties of the chromophores. Glass transition temperatures of synthesized azochromophores are in the range from 37 to 60 °C. Nonlinear optical properties of synthesized azochromophores were characterized by second harmonic intensity measurements in corona poled thin films of pure amorphous solids. Nonlinear optical coefficient d33 values for molecular glasses containing single azochromophore were in the range from 20.2 to 50.5 pm⋅V −1 . Highlights: Dendronized azobenzene shows arene-perfluoroarene interactions in a single crystal. Arene-perfluoroarene interactions influence nonlinear optical properties. Molecular glasses of pure compounds have high polar order of poled films.